Optimasi Multiple Travelling Salesman Problem Pada Pendistribusian Air Minum Menggunakan Algoritme Particle Swarm Optimization (Studi Kasus: UD. Tosa Malang) - Rinindya Nurtiara Puteri; Agus Wahyu Widodo; Imam Cholissodin (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
If the distribution application was not run optimally ,it can obstruct the distribution of drinking water process.The tardiness of drinking water transmission become an obstacle in the process and it is also effected by many factors, such as sales ignorance about the shortest path to where the customers are.So this system can lead and make the process easier to determine the shorthest path. In that Distribution obstacle we called it Multiple Travelling Salesman Problem because implicate more than one factor .One of the main purpose from this research is to determine the shortest path for every saleses.This thesis uses Particle Swarm Optimization Algorithm. There were some thesis talked about Multiple Travelling Salesman Problem but to PSO method is scarce. Particle Swarm Optimization is one of the method that solved M-TSP which is that method will gives some effective solutions.Based on the background,researcher choose to use The optimization of Multiple Travelling Salesman Problem application,and in drinking water distribution use Particle Swarm Optimization Algorithm. The result that had been proved show the route sequence that used is better from optimum parameter made 30 iterations and with 90 particle.